Transformational Leadership and Self-Discipline Strategies in Student Organizations - Cecep Sobar Rochmat; Dina Rahayu Meylasari; Nur Alya Yusra (Managere: Indonesian Journal of Educational Management, 2025)
This study examines the dynamics of transformational leadership and self-discipline among student leaders of DEMA UNIDA Gontor (Student Executive Board of UNIDA Gontor), an Islamic higher education institution with a pesantren-based environment. Using a qualitative phenomenological approach, the research collected primary data through in-depth interviews with seven student leaders who actively manage organizational programs and responsibilities. Additional observational data were gathered from Leadership training activities and routine organizational meetings to enrich the contextual understanding of Leadership practices and the formation of discipline. The findings reveal that transformational Leadership is consistently reflected through clarity of vision, moral exemplification, encouragement of creativity, and opportunities for members to grow. At the same time, self-discipline emerges as a fundamental mechanism that supports fulfilling organizational duties, particularly through daily planning, prioritization, avoiding procrastination, and consistent time management. The integration of these two elements forms a leadership model that is value-oriented, participatory, and rooted in Islamic principles of amanah and adab. Furthermore, the study highlights that self-discipline not only strengthens organizational effectiveness but also contributes to the character formation of student leaders within the pesantren culture. These findings provide important implications for leadership development in student organizations, emphasizing the need for integrated leadership training that combines vision, role modeling, and structured discipline.